Oral varespladib for the treatment of snakebite envenoming in India and the USA (BRAVO): a phase II randomised clinical trial - Chanaveerappa Bammigatti; Timothy F Platts-Mills; Ashish Bhalla; Harish Kumar; Matthew R Lewin; Surendra Kumar; Charles J Gerardo; Rebecca W Carter; Farshad M Shirazi; Suneetha D Kotehal; Peter D Akpunonu; Richard B Schwartz; et al. (BMJ Global Health)
Introduction Snakebite envenoming (SBE) results in over 500 000 deaths or disabling injuries annually. Varespladib methyl, an oral inhibitor of secretory phospholipase A2, is a nearly ubiquitous component of snake venoms. We conducted a phase II clinical trial to assess efficacy and safety of oral varespladib methyl in patients bitten by venomous snakes.Methods This double-blind, randomised, placebo-controlled trial enrolled patients in emergency departments in India and the USA. Patients with SBE were randomly assigned (1:1) to receive varespladib methyl or placebo two times per day for 1 week. All patients received standard of care, including antivenom. The primary outcome was change in the composite Snakebite Severity Score (SSS) measuring the severity of envenoming, from baseline to the average composite SSS at 6 and 9 hours.Results Among 95 patients randomised August 2021 through November 2022, the most common snakebites were from Russell’s vipers (n=29), copperheads (n=18) and rattlesnakes (n=14). The SSS improved from baseline to the average at 6 and 9 hours by 1.1 (95% CI, 0.7 to 1.6) in the varespladib group versus 1.5 (95% CI, 1.0 to 2.0) in the placebo group (difference −0.4, 95% CI, −0.8 to 0.1, p=0.13). While key secondary outcomes were not statistically different by treatment group, benefit was seen in the prespecified subgroup initiating study drug within 5 hours of bite (n=37). For this early treatment group, clinically important differences were observed for illness severity over the first week, patient-reported function on days 3 and 7 and complete recovery. No death or treatment emergent serious adverse event occurred.Conclusion For emergency department treatment of snakebites, the addition of varespladib to antivenom did not find evidence of difference for the primary outcome based on the SSS. A potentially promising signal of benefit was observed in patients initiating treatment within 5 hours of snakebite.